2016
DOI: 10.1037/emo0000181
|View full text |Cite
|
Sign up to set email alerts
|

Don’t like what you see? Give it time: Longer reaction times associated with increased positive affect.

Abstract: Images with an ambiguous valence (e.g., surprised facial expressions) are interpreted by some people as having a negative valence, and by others, as having a more positive valence. Despite these individual differences in valence bias, the more automatic interpretation is negative, and positivity appears to require regulation. Interestingly, extant research has shown that there is an age-related positivity effect such that relative to young adults, older adults attend to and remember positive more than negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 52 publications
21
70
0
Order By: Relevance
“…Also, a pattern similarity analysis revealed that individuals with a negative valence bias showed amygdala responses to surprised faces that were similar to maintaining negative affect towards negatively valence IAPS scenes during an emotion regulation task. Taken together, this study supports the prevailing hypothesis that positive interpretations of ambiguous stimuli involve mechanisms common to reappraisal during explicit emotion regulation (Neta and Tong, 2016), and is consistent with the notion that negative interpretations tend to be the initial response (Kim et al , 2003; Kaffenberger et al , 2010; Neta and Whalen, 2010; Neta et al , 2011). …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Also, a pattern similarity analysis revealed that individuals with a negative valence bias showed amygdala responses to surprised faces that were similar to maintaining negative affect towards negatively valence IAPS scenes during an emotion regulation task. Taken together, this study supports the prevailing hypothesis that positive interpretations of ambiguous stimuli involve mechanisms common to reappraisal during explicit emotion regulation (Neta and Tong, 2016), and is consistent with the notion that negative interpretations tend to be the initial response (Kim et al , 2003; Kaffenberger et al , 2010; Neta and Whalen, 2010; Neta et al , 2011). …”
Section: Discussionsupporting
confidence: 90%
“…Additionally, all participants were Caucasian to control for any cross-race effects when making judgments about emotional expressions of Caucasian faces. Three participants were excluded because they failed to provide accurate ratings of clearly valenced faces (angry, happy) on at least 60% of trials, as in previous work (Neta et al , 2009, 2013, 2018; Neta and Tong, 2016; Brown et al , 2017). Three additional participants were removed because they did not complete the neuroimaging portion of the task, resulting in a final sample of 51 participants (26 female; ages 17–30 years, mean age = 20.7, s.d.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations